Ensuring sustainability of software tools and services by cooperation with a research infrastructure. (January 2016) - Kuchinke, Wolfgang; Ohmann, Christian; Stenzhorn, Holger; Anguista, Alberto; Sfakianakis, Stelios; Graf, Norbert; Demotes, Jacques
Sustainability of project output and especially of the maintenance and further development of software is of growing concern for the research community. In the personalized medicine project p-medicine solutions that address this sustainability problem were developed and discussed in a workshop. They involve a number of interrelated and mutually supportive measures including the creation of a service center, building modular software, using common data standards, mutual service exchange with a research infrastructure, Open Source and fee-based software provision, joint promotion and deployment of tools in a regulated, clinical trial situation. These ideas join a nascent literature seeking to understand how project output can be put into a sustainable environment and to suggest solutions that may be useful for academic projects in general.